The role of arousal regulation biofeedback exercise on improving the performance of skilled shooters - Hosseiny, S. H.; Vaezmousavi, M. (Journal of Advanced Sport Technology, 2022)
Improving athletic performance through biofeedback training has been observed in some studies. Findings related to the relationship between arousal and performance are limited and more research is needed to reach a definitive conclusion. This study aimed to investigate the effects of arousal regulation practice on the performance of skilled shooters. 12 skilled shooters air rifle 10 (m) volunteered to participate in the study. After the pre-test shooting, the 10 shooters who scored the entry point were divided into two groups of five, experimental and control, as the only subjects available. The shooters of the experimental group participated in three sessions of arousal regulation training and then in five sessions of shooting practice, emphasizing reducing the level of arousal to the baseline. But the subjects in the control group practiced in these five sessions in the same way as usual. Then both groups participated in the post-test and shooting transfer test. The arousal training program was developed with the help of a biofeedback specialist. Shooting tests were performed by the conditions of the official shooting competitions. The results of repeated measures analysis of variance test showed that the score of shooters in the experimental group in the post-test and shooting transfer test increased significantly a = 0.05. In addition, the arousal level of the last half-second of the last shots of the experimental group was significantly lower than the level of arousal of the last half-second of their first shots in a total of five shooting practice sessions a = 0.05. The results of the study, confirming the ability to learn to regulate arousal, showed that due to biofeedback training, control over physiological responses is increased and the sympathetic system is turned off and the parasympathetic system is activated. As a result, athletic performance is improved through self-regulation of arousal. The findings of this study can be explained by the theory of Reversal.